Survey on Students’ Interest and Motivation in Participating in the Pencak Silat Extracurricular Activity in Elemtary Schools Throughout the Talun District - Rahmat, Basuki; Hary, Valentino; Fauzen, M. Nur Ridwan; Nohantiya, Peni (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
This study aims to analyze students' interests and motivations in participating in pencak silat extracurricular activities in elementary schools in Talun District. The study used a quantitative descriptive approach by involving 106 students who actively participated in pencak silat extracurricular activities as respondents. The sample determination technique uses purposive total sampling so that all members of the population are used as research samples. Data collection was carried out through the distribution of questionnaires supported by interviews and documentation to obtain more comprehensive information about students' interests and motivations. The research data was analyzed using descriptive statistical techniques in the form of percentages. The results of the study showed that students' interest and motivation in participating in pencak silat extracurricular activities were in the very high category with an average percentage of 85.64%. These findings show that pencak silat extracurricular activities receive a very positive response from students and are able to attract their participation in a sustainable manner. The results of this research are expected to be evaluation and consideration materials for schools and trainers in designing, developing, and improving the quality of pencak silat extracurricular programs so that they remain in accordance with the needs, interests, and motivations of students